A macro-modelling approach for the analysis of infilled frame structures considering the effects of openings and vertical loads. Issue 5 (3rd May 2016) - Asteris, Panagiotis G.; Cavaleri, Liborio; Di Trapani, Fabio; Sarhosis, Vasilis
Abstract : During the last decades, several macro-models have been proposed for the modelling of the infill panels' contribution to the lateral strength of frames. Despite all this effort, a robust model, which takes into account the influence of the vertical load, is not yet available. Furthermore, the influence of the very common case of infill walls with openings, such as windows and doors, has been neglected in all the code provisions that have been published so far. In this paper, an updated macro-model, based on the equivalent pin-jointed diagonal compressive strut, is presented. The proposed macro-model is able to represent the stiffening effect of the infill panel with openings by taking into account both the size of the opening and the vertical load acting on the frame. Detailed and in-depth parametrical investigation, based on finite element analysis, shows that the proposed mathematical macro-model can be used as a reliable and useful tool for the determination of the equivalent compressive strut width since it accounts for a large number of parameters, which are not generally accounted for by the already available models in the literature.